The benign mimickers of carcinoma on breast MRI - Durur Subaşı, Irmak; Karaman, Adem; Demirci, Elif; Şipal, Sare; Akçay, Müfide Nuran (ValpoScholar-Valparaiso University, 2022)
The similarity between benign and malignant pathologies on magnetic resonance imaging (MRI) and a wide-ranging variability of the lesions from benign proliferative changes to invasive breast carcinoma cause a lower and wide-ranging specificity of breast MRI relative to its surpass sensitivity. A wide range of tissue components such as the skin, the adipose tissue, vascular and neural tissues, connective tissues, glandular tissues, ducts, and muscle tissues are found here all together. This pictorial review was aimed at deliberating benign mimickers of breast carcinoma on MRI and trying to call attention to the overlapping and distinctive features.
Keywords: Breast Tumors; Breast Carcinoma; Breast; Magnetic Resonance Imaging